NEW TRENDS IN ECONOMIC FORECASTING - NICOLAE MARIUS JULA; NICOLETA JULA (Challenges of the Knowledge Society)
Economic forecasting is a dynamic domain. New methods are developed and tested and the methodology needs to be updated according to economic reality. Classical approach in methodology must be completed with latest trends in econometric analysis and the forecasting methods have to benefit from the increasing computational power of the modern software. One of the main causes of false prediction is using altered data. In this paper, we will present the new concepts for data testing, adjusted for the Romanian economy, based on Benford's law.